Portrait of Public Policy Formulation on Local Taxes in Bekasi City - Kusuma, Michael; Utomo, Rachmad; Rebeca, Brigitha Mega (Journal of Social and Policy Issues, 2025)
This research aims to analyze the implementation and obstacles in the public policy formulation of local tax regulations in Bekasi City. Employing a descriptive qualitative method with a case study approach, data were collected through interviews with purposively selected policy-formulating informants and analyzed using the Miles and Huberman interactive analysis model. The research results showed that the policy formulation process went through four stages (problem identification, policy agenda, alternative selection, and policy determination) but was marked by four main obstacles: time management, incompetence of human resources, differing actor agendas, and prevailing rules and procedures. This research contributes empirical evidence on how contextual factors, such as legal deadlines and local political dynamics, can impede policy formulation at the regional level, offering practical implications for local governments to improve management capacity and institutional coordination.